King Henry IV part 1 - Shakespeare, William, 1564-1616. 4 0 16; 5 (London : Arden Shakespeare, 2002)
David Scott Kastan's lucid exploration of the remarkable richness and ambitious design of 'King Henry IV part 1' reveals the play to be almost a treatise on the central relationship between value and political authority.
List of illustrations -- General Editors? preface -- Preface -- Introduction -- Great expectations -- Mingling kings and clowns: history, comedy and dramatic -- unity 1 Henry 4: one part or one play? -- Understanding politics in the play -- Understanding the politics of the play -- Unimitated, unimitable Falstaff -- Falstaff as Oldcastle/Oldcastle as Falstaff: radical -- Protestantism and Rabelaisian play -- Counterfeiting and kings, credit and credibility: economic language in the play -- What is that word ?honour?? -- Women in the play -- The play in performance -- The play on the page: the text of 1 Henry 4 -- Editorial procedures -- King Hen45 IV, Part One -- Appendix 1: The sources of 1 Henry IV -- Appendix 2: A note on Shakespeare?s metrics -- Appendix 3: The play in manuscript -- Appendix 4: Casting -- Appendix 5: The Q0 fragment -- Abbreviations and References -- Index
Includes bibliographical references (pages 368-385) and index.
Keywords: 2 -- 0; 6; Drama. -- Shakespeare, William, 1564-1616. King Henry IV. Part 1.;Henry IV, King of England, 1367-1413; 20; 2